2020
DOI: 10.3390/ijerph17041226
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Resilience of Different Farming Strategies in Coping with Geo-Hazards: A Case Study in Chongqing, China

Abstract: Adjusting farming strategies are adaptive behaviors to cope with hazard risks. However, few studies have studied rural and remote mountain areas in China with little known about “farmers’ adaptation under the impact of geo-hazards”. Unlike traditional farmers’ behavioral adaptation studies, in this study, we focused on the resilience of farmers’ behavioral mechanisms to address local hazards such as geo-hazards. Our data were acquired through questionnaire responses (N = 516) in mountainous hazard-prone areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In the survey, it was found that most farmers are more inclined to participate in free DM activities, such as escape drills. This finding is similar to that of Peng et al (2019, 2020). They found that the factor that affected farmers' ability to adjust their crops was lack of money; factors that discourage farmers from buying disaster insurance also include economic costs.…”
Section: Theory and Hypothesissupporting
confidence: 93%
“…In the survey, it was found that most farmers are more inclined to participate in free DM activities, such as escape drills. This finding is similar to that of Peng et al (2019, 2020). They found that the factor that affected farmers' ability to adjust their crops was lack of money; factors that discourage farmers from buying disaster insurance also include economic costs.…”
Section: Theory and Hypothesissupporting
confidence: 93%
“…The above studies have mainly focused upon the livelihood resources available to rural residents, but less attention has been paid to the impact of rural residents’ interactions with the external environment upon livelihood resilience. However, some scholars have constructed a new research framework that incorporates the adaptive capacity [ 23 , 39 ], or disaster resilience [ 7 , 40 ], of rural residents, arguing that the ability to choose livelihood strategies in response to changing external conditions is equally critical. On this basis, LRRR could be measured through disturbance, sensitivity, and adaptability at the farm level [ 41 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared to rural residents, urban residents have higher levels of livelihood and better livelihood security [ 5 ]. This is mainly because, firstly, rural residents principally depend upon agricultural income, and the agricultural economy is extremely susceptible to environmental changes and human activities [ 6 , 7 ]. In general, rural residents have lower incomes, less social capital, and are less advantaged in the face of abrupt political or economic changes and devastating natural disasters than are urban residents, who have more opportunities for education and employment [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of experts try to break down resilience into several dimensions of ability or capacity [47]. Resilience is acknowledged as adaptability [24,48,49], recoverability (preventive and protective) [50][51][52], anticipation [50][51][52][53][54], and innovation level [54][55][56][57]. While organizational theory approaches resilience measurement by assessing the ability of systems to detect, respond, and adapt to disturbances [58] and defend themselves in the midst of a challenging environment and then recover from the after-efects [53].…”
Section: Introductionmentioning
confidence: 99%